Mitigation of Oxygen Stress and Contamination-free Cultivation in Microalga Cultures - Peng, Licheng (Université d'Ottawa / University of Ottawa, 2016)
Microalgae are promising candidates for biofuel production, CO2 biomitigation, and production of a variety of value-added products. However, high production costs and large energy consumption have been a major concern hindering the commercialization of microalgal products and processes. In addition, biological contamination and oxygen stress are two of the major contributors to these challenges. The objective of this project was twofold: 1) developing a novel strategy for control of biological contamination to enable non-sterile cultivation of microalgae such as N. oleoabundans, and 2) developing advanced deoxygenation mechanisms to reduce oxygen accumulation in the culture. It was found that addition of appropriate amount of NaHCO3 could effectively inhibit the growth of protozoa while its inhibition on microalgae was much less and could be alleviated by increasing pH to an appropriate level. It was also found that adding 160 mM NaHCO3 in media or decreasing incident light intensity to 100 W/m2 would help alleviate the oxidative stress to cells at 400% of air saturation. The feasibility of contamination-free non-sterile cultivation of freshwater green alga N. oleoabundans was verified using long-term continuous cultivation in a 15-liter TPBR with non-sterile medium and aeration. Furthermore, localized oxygen removal using hydrophobic hollow membranes was found to effectively reduce dO2 and increase lipid accumulation. These results have the potential to be translated into low-cost cultivation of freshwater microalgae processes for production of value-added microalgal products. At a more fundamental level, the mechanisms of the inhibition of NaHCO3 on microalgae and protozoa were discussed. Efforts were also made to simulate the effects of incident light intensity on light distribution, cell growth kinetics, and lipid accumulation of N. oleoabundans under non- sterile cultivation conditions.
Keywords: Mitigation; Oxygen stress; Localized oxygen remover; Contamination-free cultivation; Freshwater microalga; Neochloris oleoabundans